Early intra-treatment diffusion weighted magnetic resonance imaging in patients with recurrent nasopharyngeal carcinoma treated with nivolumab - So, Tiffany Y.; Ai, Qi-Yong; Ma, Brigette B.Y.; King, Ann D. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Immune check point inhibitors have demonstrated promising efficacy in patients with recurrent or metastatic nasopharyngeal carcinoma (NPC) in phase I and phase II trials. Early identification of treatment response is important in these patients. This report aimed to document the early intratreatment diffusion weighted magnetic resonance imaging (DW-MRI) findings in NPC patients following treatment with the programmed cell death-1 inhibitor, nivolumab. Two consecutive patients with histologically confirmed recurrent undifferentiated NPC treated with nivolumab were prospectively recruited. Nivolumab was administered at a dosage of 3 mg/kg intravenously every 2 weeks. Patients underwent magnetic resonance imaging examinations at baseline, and at 3 and 5 weeks after commencement of treatment. Intratreatment changes in tumour volume and apparent diffusion coefficient (ADCmean)were calculated. The endpoints were objective response by response evaluation criteria in solid tumors and survival. In patient 1, an intratreatment ADC increase at 5 weeks corresponded with anatomical tumour volume reduction and a better long-term survival outcome (progression free survival 1.3 years, overall survival 2.9 years). In patient 2, an intratreatment ADC decrease at 5 weeks corresponded to progressive disease and worse outcome (progression free survival 0.0 years, overall survival 0.9 years). Intratreatment ADC changes at 3 weeks were not associated with response outcome. These cases suggest that intratreatment changes in ADC at 5 weeks may potentially predict tumour response in patients treated with nivolumab. Dedicated studies are needed to clarify these findings and fully characterise patterns of treatment related ADC change.